Bipolar disorder and risk of Parkinson disease: A nationwide longitudinal study. (11th June 2019) - Huang, Mao-Hsuan; Cheng, Chih-Ming; Huang, Kai-Lin; Hsu, Ju-Wei; Bai, Ya-Mei; Su, Tung-Ping; Li, Cheng-Ta; Tsai, Shih-Jen; Lin, Wei-Chen; Chen, Tzeng-Ji; Chen, Mu-Hong
Abstract : Objective: To evaluate the risk of Parkinson disease (PD) among patients with bipolar disorder (BD). Methods: Using the Taiwan National Health Insurance Research Database, we examined 56, 340 patients with BD and 225, 360 age- and sex-matched controls between 2001 and 2009 and followed them to the end of 2011. Individuals who developed PD during the follow-up period were identified. Results: Patients with BD had a higher incidence of PD (0.7% vs 0.1%, p < 0.001) during the follow-up period than the controls. A Cox regression analysis with adjustments for demographic data and medical comorbid conditions revealed that patients with BD were more likely to develop PD (hazard ratio [HR] 6.78, 95% confidence interval [CI] 5.74–8.02) than the control group. Sensitivity analyses after exclusion of the first year (HR 5.82, 95% CI 4.89–6.93) or first 3 years (HR 4.42; 95% CI 3.63–5.37) of observation showed consistent findings. Moreover, a high frequency of psychiatric admission for manic/mixed and depressive episodes was associated with an increased risk of developing PD. Conclusion: Patients with BD had a higher incidence of PD during the follow-up period than the control group. Manic/mixed and depressive episodes were associated with an elevated likelihood of developing PD. Further studies are necessary to investigate the underlying pathophysiology between BD and PD.